Towards an Asean Worldview: Beyond Language, Culture and other Challenges - Ojurongbe, Samuel Ayodele (International Journal of Applied Research and Sustainable Sciences, 2024)
The paper attempts a search   for a predominant worldview to drive the ASEAN vision. It recognizes   the seemingly complex and diverse backgrounds from which ASEAN member countries emerged, but believes that for resounding impact to be made, the body must have presuppositions representing the lens through which its view of life is seen.  In the face of possible policy imperatives of harnessing resources of member states and forging inclusiveness   with a regional approach, it raises the critical   concern of addressing the   identity   issue of ASEAN, without which the community will not go beyond the elite level. It opines that   only at the grassroots level will all inherent challenges and possible dangers that might ensue from the community   be   effectively addressed. Against the backdrop of diversity of language, culture, religion, government and other social structure, the paper believes that   ASEAN member states share some destinies which include unemployment, inequality, high population growth, ethnic conflicts, environmental degradation, malnutrition and poverty. The images of diversity and the rallying point of shared destinies seem like arrows pointing in one direction, and also present another profound revelation: the dynamics of interaction in all of the ASEAN countries are directly related to the communication pattern that consequently produced their economic downturn.  The paper concludes that a worldview anchored on the unifying factors of the shared destinies among ASEAN member states, and the strong shield for their realization in DEVCOM, may provide the needed wisdom and perspective for an ASEAN worldview.